The roles of spirituality and morality in human capital development - Haroon Ali Gindo; Zakaria Stapa; Muhammad Hakimi Mohd. Shafiai (Penerbit Universiti Kebangsaan Malaysia, 2018)
This study pertains to the relevance of spirituality and morality in Human Capital Development. The Conventional Economic Theories do not regard morality as an essential component of their principles; they consider material good as the end, and the end justifies the means. Moral issues like justice, honesty and fairness are treated as outside elements to be used by the state only to correct the short comings of the market transactions. This grave error is the result of their misunderstanding of what constitute ‘human-self’ and, therefore, what is to be considered as ‘self-interest’. What they describe as ‘self’ is infact the ‘Ego-self’; which is the lower part of human spirit, and that which theologians have described as ‘animalistic soul’. The conventional economist failed to recognize the human ‘Angelic-spirit’ in their definition of human-self, that which is the essence and the bearer of human moral faculties. The implication of such error is that moral aspect of human-being is ignored, and ‘Self-interest’ is, now, confused with egoistic behavior and selfishness in the conventional economics. As a result, the states that practice these economic systems have seen alarmingly disproportionate distribution of wealth, and exploitation and deception have become a normal means to the end. The objective of this study thus is to explain the link between spirituality and morality, as the former is the source of the latter. To explain how the concept of Human Capital directly impacts the economic transaction. To analyze how spiritual faculties govern our moral values, and why morality must be included in the definition of Human Capital in conventional economics and transactions. The method of the study is qualitative; it analyzes the perspectives of the conventional economist and that of the theologians of Abrahamic Religions Islam, Christianity and Judaism on what constitute ‘Human-self’ and human ‘Innate abilities’ that are vital for Human Capital Development Programs. It concludes that the definition of ‘human-self’ needs adjustment and ‘self-interest’ must include ‘moral-interest’, and that morality must be internally cultivated for the achievement of socially responsible Human Capital.